Dynamique De La Végétation De Bamo Et Stocks De Carbone Dans La Mosaïque De Végétation - M. Anobla, Adingra Odette Marie; N’Dja, Justin Kassi (European Scientific Journal, ESJ, 2016)
This study was conducted in Agboville, Ivory Coast. The objective was (1) to characterize the floristic composition, dynamics, and structure of tree diversity of postcultural fallows; and (2) establish the relationship between the diversity and storage of carbon in timber biomass. The study relied on a network of 50 temporary plots. There were 31 postcultural fallows and 19 plots of primary forest. This study has identified 417 plant species distributed in 306 genera and 83 families. Tree density within postcultural fallows varied between 1025 to 5975 stems / ha, and the analysis showed that the density increases with the age of the postcultural fallows. Tree sampling was non-destructive and to estimate C storage, an allomectric models for above and belowground biomasses was used. Mean estimate of carbon (C) stocks in biomass were 80.25 tC / ha for groupe A (fallows from 4 to 8 years) and 256.5 tC / ha for group D (fallows from 14 to 24 years). These values remain far below those seen in the groups of primary forests with lateritic soil (1335.25 tC / ha). Results showed the ability of some postcultural fallows to store much C. It demonstrated that storage depends mainly on age and conserved species. This supports the idea of employing REDD+ processes in enhancing the ecological value associated with carbon.